2013
DOI: 10.1002/jbm.b.33057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors in thein vitrodehydration of hydrogel and silicone hydrogel contact lenses

Abstract: Lower RH seems to increase CL dehydration being further accelerated with the AF presence. The dehydration pattern is material dependent, thus current marketed CLs behave differently under several controlled environmental conditions. Future in vivo studies should confirm these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
2
13
1
Order By: Relevance
“…Under this highly constricted condition, and taking into account that the water confined does not interact, or interact quite weakly with the surface, water diffusion is slower in hydrophobic channels than in bulk water, at least when lens is exposed to low HR% environments. This might be relevant in the behaviour of hydrogel and silicone hydrogel contact lenses as they are subjected to dehydration at the ocular surface, and particularly when the environmental conditions change …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under this highly constricted condition, and taking into account that the water confined does not interact, or interact quite weakly with the surface, water diffusion is slower in hydrophobic channels than in bulk water, at least when lens is exposed to low HR% environments. This might be relevant in the behaviour of hydrogel and silicone hydrogel contact lenses as they are subjected to dehydration at the ocular surface, and particularly when the environmental conditions change …”
Section: Discussionmentioning
confidence: 99%
“…A recent work published by Martín–Montañez et al showed that among diverse conventional hydrogel and silicone hydrogel lenses, Comfilcon A was the lens with faster evaporation rates after exposure to extreme environmental conditions of low RH and high temperature. However, a comparison between Si‐Hy lenses demonstrates that water flux and transmissibility values decrease when the EWC decreases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that conventional hydrogels have always incorporated higher water content in order to achieve higher oxygen permeability. However, high water content contact lenses tended to dehydrate to a higher degree, thereby causing certain physiological disorders . Therefore, in order to avoid physiological complications, manufacturers designed thicker contact lenses, which led to a reduction of oxygen transmission and an increase in potential mechanical complications.…”
mentioning
confidence: 99%
“…The silicon‐based polymer polydimethylsiloxane (PDMS) has received significant attention because of its several appealing properties such as good optical transparency, high gas permeability, nontoxicity, biocompatibility, and heat resistance. Due to these advantages, PDMS‐based elastomers have been widely used as biocompatible devices (eg, contact lenses), micro fluidic devices, and drug delivery carriers . However, the hydrophobic nature of the surface confines its wide use in some applications, particularly for biocompatible devices, because some hydrophobic molecules, proteins, and cells are easily absorbed to the surface.…”
Section: Inroductionmentioning
confidence: 99%